An introduction to applied linguistics (Routledge, Taylor & Francis Group, 2020)
An Introduction to Applied Linguistics provides a complete, authoritative and up-to-date overview of the state of the field. Divided into three sections covering: a description of language and language use; essential areas of enquiry; and language skills and assessment